Outside looking in [compact disc, unabridged] - Boyle, T. Coraghessan (Harper Audio, 2019)
In 1943, LSD is synthesized in Basel. Two decades later, a coterie of grad students at Harvard are gradually drawn into the inner circle of renowned psychologist and psychedelic drug enthusiast Timothy Leary. Fitzhugh Loney, a psychology Ph.D. student and his wife, Joanie, become entranced by the drug's possibilities such that their 'research' becomes less a matter of clinical trials and academic papers and instead turns into a free-wheeling exploration of mind expansion, group dynamics, and communal living.